ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI HAND AND FOOT MASSAGE DALAM PENURUNAN SKALA NYERI PADA IBU POST SEKSIO SESAREA - Rensi Hepi Farenta (2023)
Caesarean section is a surgical procedure performed to give birth to a baby by making an incision in the mother's abdominal wall and uterine wall. Caesarean section often cause pain in the incision area. Pain if not treated immediately will have several impacts, one of which is disruption of the ability to carry out daily activities due to limited mobility of the mother or it can also cause the mother to not be optimal in breastfeeding and caring for her baby. Hand and foot massage therapy is a non-pharmacological technique that can be applied to treat acute pain in women after caesarean section. Respondents in this study consisted of 1 patient who was managed (intervention) and 1 patient who was continued (control). Hand and foot massage therapy is carried out three times with a frequency of once per day for 20 minutes. The pain scale will be measured using a Visual Analog Scale (VAS) pain aid before the intervention is carried out, immediately after the intervention is given, then it is measured again 30 minutes and 60 minutes after the intervention is given. The results of this study were that in under management patients the pain scale decreased to a scale of 1 from a scale of 7 after being given additional hand and foot massage therapy. Whereas in resume patients who did not receive hand and foot massage therapy, the pain scale was 3 out of 7. Conclusion: The pain scale at 30 minutes after the massage was significantly lower than before the massage was performed and even though the pain scale at 60 minutes after the massage was again increased, it was still lower than before the massage. This proves that hand and foot massage therapy is effective as a non-pharmacological therapy in reducing the pain scale after caesarean section.